(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Тhe article is devoted to the experience of China’s policy in the spheres of international economy and collective security within such organizations, as Shanghai Cooperation Organization. There is given an analysis on whether Chinese foreign policy concept in today’s era of globalization is sustainable enough for it to become the world’s second superpower, and on the main directions forming the basis of its promotion. Also, we can see the analysis of the methods which are used by Chinese government in such directions like USA, EU, Russia and the evolution of Chinese political, economic and financial relations with major powers of today.The author gives own proposals on the most profitable way of evolving the foreign political course of China and gives variations of possible consequences and results which might take place depending on the concept that Chinese government chooses. Key words: сollective security, globalization, geopolitics, region, cooperation.